Spinal Dural Arteriovenous Fistulas Are Not Associated With Prothrombotic Factors - Jellema, K.; Tijssen, C.C.; Fijnheer, R.; de Groot, P.G.; Koudstaal, P.J.; van Gijn, J. (Stroke (1970), 2004)
Background and Purpose— The cause of spinal dural arteriovenous fistulas (SDAVF) is unknown. In intracranial dural arteriovenous fistulas, an association with factor V Leiden mutation has been found. Therefore, we studied the association between prothrombotic factors and SDAVF. Methods— Factor V Leiden mutation, factor II mutation, protein S, protein C, factor VIII, von Willebrand factor, antithrombin III, and lupus anticoagulant were determined by means of standard laboratory tests in 40 patients and 119 control subjects matched for sex and age. Results— Factor V Leiden mutation was not found in the patient group and was found twice in the control group. Factor II mutation was found in 1 patient and in none of the control subjects. There was no decreased activity of protein S, protein C, factor VIII, von Willebrand factor, or antithrombin III in patients in comparison with controls. Lupus anticoagulant was not found in the patient group and once in the control subjects. Conclusions— We conclude that it is unlikely that prothrombotic factors are involved in the pathogenesis of spinal dural arteriovenous fistulas, but subtle associations are not ruled out.